The Urgency of Spiritual Care Training for Islamic Chaplains - Jarir Idris; Anni Nurul Hidayati (SUHU: Journal of Sufism and Humanities, 2026)
Objective: This article examines the urgency of spiritual care training for newly appointed Islamic chaplains and its contribution to strengthening their professional competencies in healthcare and social service settings in Indonesia. Method: This study employs a library research approach by critically reviewing scholarly literature on spiritual care, chaplaincy education, holistic healthcare, and the competencies required of Islamic chaplains. The data were analyzed using qualitative content analysis to identify major themes related to training needs and competency development. Results: The findings reveal that the increasing demand for services addressing patients’ physical, psychological, social, and spiritual needs has positioned spiritual care as an essential component of patient-centered healthcare. Nevertheless, Islamic chaplains in Indonesia continue to face challenges, including the lack of standardized competency frameworks, systematic training curricula, and professional practice guidelines. The reviewed literature indicates that structured spiritual care training significantly improves chaplains’ knowledge, practical skills, and professional competencies in assessing spiritual needs, delivering appropriate spiritual interventions, communicating religious values with cultural and spiritual sensitivity, providing emotional and existential support, and collaborating effectively within multidisciplinary healthcare teams. Furthermore, such training facilitates the internalization of core Islamic values, including ṣabr (patience), tawakkul (trust in God), ḥusn al-ẓann (positive regard toward God and others), compassion, and sincerity, into professional practice. Conclusion: Developing and implementing a standardized Islamic-based spiritual care training program is a strategic initiative to enhance the quality of spiritual care services, strengthen the professional identity of Islamic chaplains, and address the growing need for holistic, integrated, and patient-centered healthcare and social services in Indonesia.